2014
DOI: 10.4049/jimmunol.1401268
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Superantigen Staphylococcal Enterotoxin B in Complex with TCR and Peptide–MHC Demonstrates Absence of TCR–Peptide Contacts

Abstract: Superantigens are immune-stimulatory toxins produced by Staphylococcus aureus, which are able to interact with host immune receptors to induce a massive release of cytokines, causing toxic shock syndrome and possibly death. In this article, we present the x-ray structure of staphylococcal enterotoxin B (SEB) in complex with its receptors, the TCR and MHC class II, forming a ternary complex. The structure, in combination with functional analyses, clearly shows how SEB adopts a wedge-like position when binding t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 37 publications
3
54
0
1
Order By: Relevance
“…C) 3D structure of STX and its producer, the dinoflagellate Alexandrium ostenfeldii (insert). D) Crystal structure of SEB in complex with MHC II and T cell receptor (4C56.pdb [93]) (SEB red ribbon, intrachain disulfide bridge yellow sticks, MHC II yellow ribbon, TCR green ribbon) and EM picture of Staphylococcus aureus producing SE (insert). substrates; the detection limits are mostly in the low ng/mL to high pg/mL-range [21,22].…”
Section: Ricin From Ricinus Communismentioning
confidence: 98%
“…C) 3D structure of STX and its producer, the dinoflagellate Alexandrium ostenfeldii (insert). D) Crystal structure of SEB in complex with MHC II and T cell receptor (4C56.pdb [93]) (SEB red ribbon, intrachain disulfide bridge yellow sticks, MHC II yellow ribbon, TCR green ribbon) and EM picture of Staphylococcus aureus producing SE (insert). substrates; the detection limits are mostly in the low ng/mL to high pg/mL-range [21,22].…”
Section: Ricin From Ricinus Communismentioning
confidence: 98%
“…The recently solved ternary structure of SEB in complex with HLA-DR1 and TcRVα22/Vβ19 confirmed that SEB adopts a wedgelike position when binding to the TcRVβ-chain, allowing for an interaction between the Vα chain and MHC class II (Figure 32.3a). This binding mode also circumvents contact between TcR and the presented peptide, allowing SEB to trigger a peptide-independent activation of T cells [190]. In 2002, two more complexes were determined-that of SPE-A bound to mouse Vβ8.2 and of SPE-C bound to human TcRVβ2.1 [18].…”
Section: Binding To Tcrmentioning
confidence: 99%
“…However, due to their extremely high mitogenic activity, only fragments or toxoids, i.e., SAg mutants lacking the ability to cross-link TCR and MHC-II, can be used for vaccination. The structure-function relationship of several SAgs has been resolved in the past 25 years [6,[38][39][40][41][42][43][44]. On that basis, inactivating mutations have been predicted and experimentally confirmed for a number of staphylococcal SAgs [45][46][47].…”
Section: Vaccination Against Sagsmentioning
confidence: 99%